The Effectiveness of Learning Media Digitalization on Increasing Independent for Indonesian Millenial Learners - Mahrani, Kaylifa Hasna; Falatena, Anzalna; Wahyunengsih, Wahyunengsih (Universitas Pendidikan Indonesia (UPI), 2022)
Changes that occur in social, economic, technological, and cultural arrangements along with times, require humans to be able to adapt to any changes that exist. Human development from generation to generation accompanied by modernization produces different characters from one generation to another. One of the most widely used generations today is the millennial generation which is considered very influential for society, especially in the field of education. The rapid use of technology in the world of education will be used in changing educational models, namely the growing distance and more choices of available learning resources such as e-books, and easy access to digital applications such as e-libraries, e-forums, e-journals. The purpose of this study is to find out how effective digital learning media is in increasing independence for Indonesian millennial students. This study uses a qualitative method by utilizing and a questionnaire. The results of the study show that digital learning media is quite effective in increasing learning independence for Indonesian millennial students.